Prediction Model of Drug-Induced Liver Injury in Patients with Pulmonary Tuberculosis: Evaluation of the Incidence and Risk Factors - Farzaneh Dastan; Behnam Dasht Bozorg; Ali Goodarzi; Jamshid Salamzadeh; Payam Tabarsi; Farzad Kobarfard; Fanak Fahimi (Research Center for Rational Use of Drugs (RCRUD), 2017)
Introduction and objectives: Tuberculosis (TB) still remains a major health concern both in developing and developed countries. The rate of the liver injury due to anti-TB drugs in developed countries has been reported up to 4%. The goal of this study is to assess the rate and risk factors for anti-tuberculosis drug-induced liver injury (DILI). Also, a model has been designed to predict DILI in patients with pulmonary tuberculosis. Methods: We conducted an observational study. The investigation was carried out in the National Research Institute of Tuberculosis and Lung Disease, Tehran, Iran. Anti-tuberculosis drug treatment course and patients' demographic data, medical and drug history, and social habits were extracted from their medical records. DILI was defined as an increase in serum alanine aminotransfrase (ALT) or aspartate aminotransfrase (AST) greater than three times of the upper limit of normal (ULN), with symptoms of liver injury, or five times of the ULN without symptoms. Results: In this study, 87 patients (33 male, 54 female, mean age 54.29±21.79 years) with tuberculosis diagnosis were followed. Anti-tuberculosis induced liver injury was detected in 14 (16.1%) patients. Concomitant use of hepatotoxic drugs (Isoniazid, Rifampin and Pyrazinamide) and the abnormal baseline serum liver enzyme levels before the initiation of therapy were found as risk factors for anti-tuberculosis induced liver injury. Conclusion: Anti-tuberculosis induced liver injury is a major problem in tuberculosis patients which lead to treatment interruption in 14 (16.1%) patients. Due to the lack of evidence regarding the mechanism of this side effect, we recommend to monitor anti-tuberculosis drug levels in order to study their probable correlations with DILI.